Preparation method for in-situ growth of heterojunction photocatalyst on fiber surface
A one-step method for in-situ growth of a heterojunction photocatalyst on fibers addresses the complexity and instability of existing methods, achieving high photocatalytic performance and recyclability.
Patent Information
- Application Number
- CN202411387015.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-31
AI Technical Summary
Existing methods for loading photocatalysts on fibers or fabrics are complex, have poor stability, and low activity under visible light, making them unsuitable for large-scale production.
A one-step method for in-situ growth of a heterojunction photocatalyst on fiber surfaces using zinc nitrate, polyacrylamide, CDs-TiO2, and dimethylimidazole, encapsulating CDs-TiO2 within ZIF-8 pores for firm bonding, enhancing stability and activity.
The method results in a stable, high-performance photocatalyst that can degrade organic dyes and heavy metals under visible light, facilitating easy recycling and multiple uses.
Smart Images

Figure CN119215995A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a heterojunction photocatalyst grown in situ on a fiber surface, and belongs to the field of composite photocatalytic material preparation. Background Art
[0002] Photocatalytic technology is a cheap, readily available and green advanced oxidation technology that can use solar radiation to produce highly oxidizing active species to oxidize and degrade organic dyes into non-toxic small molecules. Titanium dioxide (TiO2) is currently the most widely used photocatalyst material, but it is easy to agglomerate in water during use, affecting its photocatalytic efficiency. Metal organic framework ZIF-8 is a new type of porous material assembled by metal ions and organic ligands through coordination bonds. It has the advantages of uniform and rich catalytic sites, high specific surface area and good mass transfer capacity. Among them, the composite of TiO2 and ZIF-8 can not only achieve visible light response performance, but also promote the charge separation of the two through heterojunction. The large specific surface area of ZIF-8 provides more contact sites for pollutants and improves the efficiency of photocatalytic reaction. However, photocatalyst powder has the disadvantage of being difficult to recover and causing secondary pollution when catalytically degrading organic pollutants in water. For this reason, researchers have tried to load photocatalysts on large-scale, easily recyclable materials to solve the above problems. Among them, loading photocatalysts on fibers or fabrics has great research significance due to its convenience and low cost.
[0003] At present, there are few methods for loading various photocatalysts on fibers or fabrics, and most of them have complicated preparation processes, poor stability, and low activity of photocatalysts. For example, the patent document number CN115739183A discloses a fabric-based Ag / ZIF-8 functional material and its preparation method and application, which is formed by first growing ZIF-8 in situ on the surface of the fabric, and then putting ZIF-8 / fabric into a silver nitrate solution for oscillation and mixing to form a fabric-based Ag / ZIF-8 functional material. The oscillation and mixing method does not firmly bind silver nitrate to ZIF-8. A paper published by Wuhan Textile University, "Polydopamine-induced in-situ growth of zeolitic imidazolate framework-8 / TiO2 nanoparticles on cotton fabrics for photocatalytic performance", first loads TiO2 on the surface of carbon fiber, and then grows ZIF-8 in situ on the surface of TiO2 in a high-pressure reactor to obtain a ZIF-8 / TiO2 / CF composite photocatalytic material. The reaction process is two-step and the process is relatively complicated. In addition, Sichuan University published a paper titled "Durable ZIF-8 / Ag / AgCl / TiO2 decorated PAN nanofibers with high visible light photocatalytic and antibacterial activities for degradation of dyes", which first grows ZIF-8 in situ on the surface of PAN fibers, then loads Ag / AgCl, and finally loads TiO2 under high pressure and high temperature to form a ZIF-8 / Ag / AgCl / TiO2 / PAN composite material. These methods combine ZIF-8 and TiO2 to cellulose in two steps, and the preparation process is complicated.
[0004] Photocatalysts are usually loaded on the fiber surface by in-situ growth, so that the loaded fibers have good photocatalytic degradation performance and easy recycling. However, most methods of loading catalysts on the fiber surface have poor stability and cumbersome steps, which are not suitable for large-scale production. Finding an efficient, fast and low-cost method to prepare fiber-based composite photocatalytic materials with catalytic activity under visible light is an important prerequisite for their widespread application in the field of photocatalysis. Summary of the invention
[0005] The purpose of the present invention is to solve the problems existing in the prior art, such as the complex preparation process of the catalyst and fiber composite, the poor firmness of the catalyst and fiber combination, and the low photocatalytic activity under visible light, and discloses a preparation method for in-situ growth of heterojunction photocatalyst on the fiber surface. The present invention comprises the following steps: zinc nitrate and polyacrylamide are sequentially added to deionized water, and ultrasonically dispersed at high temperature to obtain solution A; then (carbon dot-modified titanium dioxide) CDs-TiO2 and dimethylimidazole are sequentially added to deionized water, and ultrasonically dispersed at room temperature to obtain solution B; a non-woven material is placed in solution A and ultrasonically dispersed to combine the non-woven material with zinc ions; then a sample loaded with zinc ions is placed in solution B and ultrasonically dispersed, and in the process of in-situ growth of ZIF-8 on the fiber surface, CDs-TiO2 is encapsulated into the pores of ZIF-8, and an encapsulated heterojunction catalyst is formed in situ on the fiber surface; finally, the sample is washed with deionized water and dried. The preparation method directly loads CDs-TiO2 and ZIF-8 onto the fiber surface of the nonwoven material in one step. The process is simple, the reaction is fast and efficient, the catalyst is easy to recover, and it can be reused many times. The specific preparation method includes the following steps:
[0006] 1. Add zinc nitrate and polyacrylamide into deionized water in sequence and disperse them by ultrasonication to obtain solution A.
[0007] 2. Add CDs-TiO2 and dimethylimidazole into deionized water in sequence and disperse them by ultrasound to obtain solution B.
[0008] 3. Place the nonwoven material in solution A and ultrasonicate to allow the nonwoven material to combine with zinc ions.
[0009] 4. The sample processed in step 3 is placed in solution B for ultrasonic treatment. During the in-situ growth of ZIF-8 on the fiber surface, CDs-TiO2 is encapsulated into the pores of ZIF-8, forming an encapsulated heterojunction catalyst in-situ on the fiber surface.
[0010] 5Finally, the samples were washed with deionized water and dried.
[0011] Wherein, in step 1, the molar ratio of zinc nitrate to deionized water is 1:800-1:1500, and the concentration of polyacrylamide is 0.1-0.3%.
[0012] Wherein, in step 1, the ultrasonic power is 200-400W, the time is 5-15min, and the temperature is 70-80°C.
[0013] Wherein, in step 2, the molar ratio of dimethylimidazole to deionized water is 1:40-1:80, and the concentration of CDs-TiO2 is 1-2%.
[0014] Wherein, in step 2, the ultrasonic power is 200-400W, the time is 5-15min, and the temperature is 20-35°C.
[0015] Wherein, the nonwoven material in step 3 is one or more of polypropylene fiber, polyester fiber and polyamide fiber.
[0016] Wherein, in step 3, the ultrasonic power is 200-400W, the time is 10-25min, and the temperature is 20-35°C.
[0017] Wherein, in step 4, the ultrasonic power is 200-400W, the time is 20-45min, and the temperature is 20-35°C.
[0018] Wherein, the number of times of washing with deionized water in step 5 is 3 to 5 times.
[0019] Wherein, in step 5, the drying time is 2 to 6 hours and the temperature is 60 to 80°C.
[0020] Beneficial effects of the present invention:
[0021] Compared with other inventions, the method for loading zinc ions on the fiber surface of the present invention fully mixes polyacrylamide with zinc nitrate solution under high-temperature ultrasound, which can provide strong adhesion for the fiber to load zinc ions, firmly load the zinc ions to the fiber surface, and provide more binding sites for the subsequent growth of ZIF-8, so that ZIF-8 and the fiber are more firmly bound.
[0022] Compared with the complicated processes of other inventions, the method of the present invention for combining CDs-TiO2 and ZIF-8 on the fiber surface comprises the following steps: firstly, mixing CDs-TiO2 with a dimethyl imidazole solution by ultrasonication, and then placing non-woven material fibers of negative zinc ions into the mixed solution; in the process of in-situ growing ZIF-8 on the fiber surface, since it is synthesized under ultrasonic conditions, not only can the ZIF-8 surface be uniformly loaded, but more importantly, CDs-TiO2 can be uniformly loaded into the pores of ZIF-8; since CDs-TiO2 is encapsulated in the porous structure of ZIF-8, the two catalysts are more firmly bonded; that is, the heterojunction photocatalyst CDs-TiO2 / ZIF-8 is quickly grown in-situ on the fiber surface by a one-step method, the preparation process is simple and efficient, and the problem of weak bonding between the two catalysts is solved.
[0023] The heterojunction photocatalytic material prepared by the present invention has excellent stability and high photocatalytic degradation performance under visible light for organic dyes and heavy metals. Due to the strong bonding between the catalysts and between the fiber and the catalyst, it can be recycled multiple times, thus solving the problem of difficult recycling of the photocatalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope (SEM) image of the CDs-TiO2 / ZIF-8 / PP heterojunction composite photocatalytic material obtained in Example 1.
[0025] Figure 2 This is the transmission electron microscopy (TEM) image of the CDs-TiO2 / ZIF-8 / PP heterojunction composite photocatalytic material obtained in Example 1.
[0026] Figure 3 This is the XRD pattern of the CDs-TiO2 / ZIF-8 / PP heterojunction composite photocatalytic material obtained in Example 1.
[0027] Figure 4 This is a diagram showing the photocatalytic degradation effect of the CDs-TiO2 / ZIF-8 / PP heterojunction composite photocatalytic material obtained in Example 1 on methyl orange dye.
[0028] Figure 5 This is a diagram showing the degradation effect of methyl orange dye after repeated use of the CDs-TiO2 / ZIF-8 / PP heterojunction composite photocatalytic material obtained in Example 1. DETAILED DESCRIPTION
[0029] The following is a further detailed description of a method for preparing a heterojunction photocatalyst grown in situ on a fiber surface provided by the present invention in conjunction with specific embodiments. It should be understood that the specific examples are only used to explain and introduce the present invention and cannot limit the scope of application of the present invention. Any modifications and changes made to the present invention fall within the scope of protection of the present invention without departing from the purpose and scope of the present invention.
[0030] Embodiment 1:
[0031] Step 1: Accurately weigh 1.103 g of zinc nitrate hexahydrate and 0.1 g of polyacrylamide and put them into 100 mL of deionized water solution in turn, and then transfer them to an ultrasonic thermostat with an ultrasonic power of 200 W, a time of 5 min, and a temperature of 70°C.
[0032] Step 2: Accurately weigh 1g of CDs-TiO2 and 5.7g of dimethylimidazole and put them into 100mL of deionized water solution in turn, and then transfer them to an ultrasonic thermostat with an ultrasonic power of 200W, a time of 5min, and a temperature of 20°C.
[0033] Step 3: Place the polypropylene (PP) fiber membrane in a mixed solution of zinc nitrate and polyacrylamide and ultrasonicate it at a power of 200 W, a time of 10 min, and a temperature of 20°C to make Zn 2+ Evenly load onto the PP fiber surface.
[0034] Step 4: Place the zinc ion-loaded PP fiber membrane in a mixed solution of CDs-TiO2 and dimethylimidazole for ultrasonic treatment at a power of 200 W, a time of 20 min, and a temperature of 20°C. During the in situ growth of ZIF-8 on the fiber surface, CDs-TiO2 is encapsulated into the pores of ZIF-8, forming an encapsulated heterojunction catalyst in situ on the fiber surface.
[0035] Step 5: The CDs-TiO2 / ZIF-8 / PP heterojunction composite photocatalytic material prepared in step 4 was washed with deionized water for 3 times to remove the excess unreacted substances, and then transferred to a vacuum oven for drying for 2 hours at a temperature of 60°C. The scanning electron microscopy and transmission electron microscopy images of the CDs-TiO2 / ZIF-8 / PP heterojunction composite photocatalytic material obtained in this embodiment are shown in the attached figure. Figure 1 and attached Figure 2 As shown in the figure, it can be seen that the CDs-TiO2 / ZIF-8 heterojunction catalyst is uniformly loaded on the surface of the PP fiber. Figure 3 The XRD diagram of the fiber-based photocatalytic material obtained in this example shows that the presence of the diffraction peak of the PP fiber proves that the loading of the catalyst will not change the crystal form of the PP fiber. And because PP has a strong diffraction peak, no obvious diffraction peak of CDs-TiO2 is observed, but the standard peak of ZIF-8 can be clearly seen. It may be that the CDs-TiO2 peak is weak, so it can be explained that the CDs-TiO2 / ZIF-8 / PP heterojunction photocatalytic material was successfully prepared. The photocatalytic degradation effect of the CDs-TiO2 / ZIF-8 / PP heterojunction photocatalytic material obtained in this example on methyl orange dye is shown in the attached figure. Figure 4 As shown in the figure, under the irradiation of simulated sunlight, the degradation rate of methyl orange dye can reach 98.5% within 120 minutes, and even if it is recycled for 5 times, it can still achieve a degradation effect of more than 85% ( Figure 5 ), proving that it is a good fiber-based photocatalytic material.
[0036] Embodiment 2:
[0037] Step 1: Accurately weigh 1.378 g of zinc nitrate hexahydrate and 0.2 g of polyacrylamide and put them into 100 mL of deionized water solution in turn, and then transfer them to an ultrasonic thermostat with an ultrasonic power of 300 W, a time of 10 min, and a temperature of 75°C.
[0038] Step 2: Accurately weigh 1.5 g of CDs-TiO2 and 7.6 g of dimethylimidazole and put them into 100 mL of deionized water solution in turn, and then transfer them to an ultrasonic thermostat with an ultrasonic power of 300 W, a time of 10 min, and a temperature of 25 °C.
[0039] Step 3: Place the polyester (PET) fiber membrane in a mixed solution of zinc nitrate and polyacrylamide and ultrasonicate it at a power of 300 W, a time of 15 min, and a temperature of 25 °C to make Zn 2+ Evenly loaded onto the surface of PET fiber.
[0040] Step 4: Place the zinc ion-loaded PET fiber membrane in a mixed solution of CDs-TiO2 and dimethylimidazole for ultrasonic treatment at a power of 300 W, a time of 30 min, and a temperature of 25°C. During the in situ growth of ZIF-8 on the fiber surface, CDs-TiO2 is encapsulated into the pores of ZIF-8, forming an encapsulated heterojunction catalyst in situ on the fiber surface.
[0041] Step 5: The CDs-TiO2 / ZIF-8 / PET heterojunction composite photocatalytic material prepared in step 4 was washed with deionized water for 3 times to remove excess unreacted substances, and then transferred to a vacuum oven for drying for 4 hours at a temperature of 70° C. The performance of the sample was then tested.
[0042] Embodiment 3:
[0043] Step 1: Accurately weigh 2.068 g of zinc nitrate hexahydrate and 0.3 g of polyacrylamide and put them into 100 mL of deionized water solution in turn, and then transfer them to an ultrasonic thermostat with an ultrasonic power of 400 W, a time of 15 min, and a temperature of 80°C.
[0044] Step 2: Accurately weigh 2 g of CDs-TiO2 and 11.4 g of dimethylimidazole and put them into 100 mL of deionized water solution in turn, and then transfer them to an ultrasonic thermostat with an ultrasonic power of 400 W, a time of 15 min, and a temperature of 35 °C.
[0045] Step 3: Place the polyamide (PA) fiber membrane in a mixed solution of zinc nitrate and polyacrylamide and ultrasonicate it at a power of 400 W, a time of 25 min, and a temperature of 35 °C to make Zn 2+ Evenly loaded onto the PA fiber surface.
[0046] Step 4: Place the PA fiber membrane loaded with zinc ions in a mixed solution of CDs-TiO2 and dimethylimidazole for ultrasonic treatment at a power of 400 W, a time of 45 min, and a temperature of 35°C. During the in situ growth of ZIF-8 on the fiber surface, CDs-TiO2 is encapsulated into the pores of ZIF-8, forming an encapsulated heterojunction catalyst in situ on the fiber surface.
[0047] Step 5: The CDs-TiO2 / ZIF-8 / PA heterojunction composite photocatalytic material prepared in step 4 was washed with deionized water for 3 times to remove the excess unreacted substances, and then transferred to a vacuum oven for drying for 6 hours at a temperature of 80° C. The performance of the sample was then tested.
[0048] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and improvement made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a heterojunction photocatalyst grown in situ on a fiber surface, characterized in that: Here are the steps: 1) zinc nitrate and polyacrylamide are sequentially added into deionized water and dispersed by ultrasonication to obtain solution A; 2) CDs-TiO2 and dimethylimidazole were sequentially added into deionized water and dispersed by ultrasound to obtain solution B; 3) placing the nonwoven material in solution A and ultrasonicating the solution to allow the nonwoven material to combine with the zinc ions; 4) The sample treated in step 3 is placed in solution B for ultrasonic treatment, and during the in-situ growth of ZIF-8 on the fiber surface, CDs-TiO2 is encapsulated into the pores of ZIF-8, thereby forming an encapsulated heterojunction catalyst in-situ on the fiber surface; 5) Finally, the samples were washed with deionized water and dried.
2. The method for preparing an encapsulated heterojunction photocatalyst grown in situ on a fiber surface according to claim 1, characterized in that: In the step 1), the molar ratio of zinc nitrate to deionized water is 1:800-1:1500, and the concentration of polyacrylamide is 0.1-0.3%.
3. The method for preparing a heterojunction photocatalyst grown in situ on a fiber surface according to claim 1, characterized in that: In the step 1), the ultrasonic power is 200-400W, the time is 5-15min, and the temperature is 70-80°C.
4. The method for preparing a heterojunction photocatalyst grown in situ on a fiber surface according to claim 1, characterized in that: In the step 2), the molar ratio of dimethylimidazole to deionized water is 1:40-1:80, and the concentration of CDs-TiO2 is 1-2%.
5. The method for preparing a heterojunction photocatalyst grown in situ on a fiber surface according to claim 1, characterized in that: In the step 2), the ultrasonic power is 200-400W, the time is 5-15min, and the temperature is 20-35°C.
6. The method for preparing a heterojunction photocatalyst grown in situ on a fiber surface according to claim 1, characterized in that: In the step 3), the nonwoven material is one or more of polypropylene fiber, polyester fiber and polyamide fiber.
7. The method for preparing a heterojunction photocatalyst grown in situ on a fiber surface according to claim 1, characterized in that: In the step 3), the ultrasonic power is 200-400W, the time is 10-25min, and the temperature is 20-35°C.
8. The method for preparing a heterojunction photocatalyst grown in situ on a fiber surface according to claim 1, characterized in that: In the step 4), the ultrasonic power is 200-400W, the time is 20-45min, and the temperature is 20-35°C.
9. The method for preparing a heterojunction photocatalyst grown in situ on a fiber surface according to claim 1, characterized in that: In the step 5), the washing times with deionized water are 3 to 5 times.
10. The method for preparing a heterojunction photocatalyst grown in situ on a fiber surface according to claim 1, characterized in that: In the step 5), the drying time is 2 to 6 hours and the temperature is 60 to 80°C.
Citation Information
Patent Citations
Fabric-based Ag / ZIF-8 functional material as well as preparation method and application thereof
CN115739183A
